The president's shadow - Patterson, James, 1947-; DiLallo, Richard (Patterson, James, 1947- Shadow thriller., 2025)
"One of America's iconinc thriller heroes recruits his lasting love, Margo Lane, and his great-great-granddaughter, Maddy Gomes, to join an international investigation. For over 150 years, Lamont Cranston -- and his alter ego, the Shadow -- has possessed an array of mental and physical powers: scientific skills, shape-shifting ability, and mind control. When a series of deadly natural disasters strikes the planet, he immediately sets out to identify who's responsible... A disgruntled graduate student? The power-hungry president of the Americas? Or could it be Shiwan Khan, the Shadow's fiercest enemy? The Shadow's latest adventure is also his, Maddy's, and Margo's most dangerous. Triumph or perish, they'll all rise or fall... together."--Jacket.